Modelling creep and recovery response of asphalt binders using generalized burgers model - Saboo N.; Mudgal A. (My University, 2025)
Appropriate modeling creep and response of asphalt binders can save time, and resources and efforts required for multiple experimentations. Creep compliance master-curves were obtained from short duration creep experiments on 10 different asphalt binders each at 0.1 and 3.2 kPa stress levels. It was shown that, a four Kelvin-element generalized Burger’s model could closely approximate creep and recovery response at any combination of loading and unloading cycle. A single run of dynamic shear rheometer used for conducting short time creep experiments at different temperatures, can be adequate for modeling creep and recovery response of asphalt binders. © 2018, © 2018 Taylor & Francis Group, LLC.